2007
DOI: 10.3177/jnsv.53.187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Uptake between PureSorb-Q40 and Regular Hydrophobic Coenzyme Q10 in Rats and Humans after Single Oral Intake

Abstract: Summary Coenzyme Q 10 (CoQ 10 ) is a lipid-soluble antioxidant and essential component of the mitochondrial electron transfer system in the body, and is in wide use as a functional food material and cosmetic raw material. However, as CoQ 10 is extremely lipid-soluble, absorption by the body is not easy. In general, people use soft-gel capsules in which CoQ 10 is suspended in oil, and take these capsules with food. PureSorb-Q TM 40 (P40) was developed to improve CoQ 10 processability and absorption when taken w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
2
21
1
Order By: Relevance
“…This is about 2.7-fold higher than the mean increase of serum CoQ10 concentration (approximately 3.0 g/mL) which was shown as the result of the repeated intake of a comparable amount of soft-gel capsules (4). Needless to say, the results can not be simply compared due to the different conditions; however, this is almost the same result as previously reported, that the serum CoQ10 absorption rate for P40 tablets was faster than that of the soft-gel capsules, although a different dose of CoQ10 was administered in the single dose study (9). In addition, in an other study, it is reported that when 1,500 mg/d of CoQ10 was administered repeatedly for 3 mo to Parkinson's disease patients (11), the mean increase of serum CoQ10 level for the study was about 5.3 g/mL.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is about 2.7-fold higher than the mean increase of serum CoQ10 concentration (approximately 3.0 g/mL) which was shown as the result of the repeated intake of a comparable amount of soft-gel capsules (4). Needless to say, the results can not be simply compared due to the different conditions; however, this is almost the same result as previously reported, that the serum CoQ10 absorption rate for P40 tablets was faster than that of the soft-gel capsules, although a different dose of CoQ10 was administered in the single dose study (9). In addition, in an other study, it is reported that when 1,500 mg/d of CoQ10 was administered repeatedly for 3 mo to Parkinson's disease patients (11), the mean increase of serum CoQ10 level for the study was about 5.3 g/mL.…”
Section: Discussionsupporting
confidence: 76%
“…A study of single oral intake using rats and humans has shown that, compared to lipid-soluble CoQ 10 , uptake rate and volume of CoQ 10 are significantly higher for P40 when administered both postprandially and in the fasting state ( 9 ). Considering this result, compared to soft-gel capsules as the common form for intake of lipid-soluble CoQ 10 , serum CoQ 10 concentration is expected to be higher with P40 even at the same dose; therefore, some safety concern was anticipated.…”
Section: Toxicity Clinical Trialmentioning
confidence: 99%
“…The timings of this peak are similar regardless of whether or not subjects are fasting when they take CoQ10 (16,25). In a previous rat study, serum CoQ10 also peaked 6 h after administration of CoQ10 (16), but we tested our rats earlier than 6 h after administration and found that the Tmax of serum CoQ10 occurred 2 h after administration (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…PureSorb-Q TM 40 (Water-soluble type CoQ 10 powder, CoQ 10 content is 40 w/w%; hereinafter referred to as P40), the test substance, is a product that was developed for the purposes of improving its low absorbability in the fasting state, which is derived from high lipid-solubility, and its low processability. A study of single oral intake using rats and humans has shown that, compared to lipid-soluble CoQ 10 , uptake rate and volume of CoQ 10 are significantly higher for P40 when administered both postprandially and in the fasting state ( 11 ). Considering this result, compared to soft-gel capsules, which are the common form for intake of lipid-soluble CoQ 10 , serum CoQ 10 concentration is to be expected higher with P40 even at the same dose; therefore, some safety concern was anticipated.…”
Section: Toxicitymentioning
confidence: 99%
“…P40 is not affected by meals for the absorption of CoQ10. Our previous study of rats and humans showed that CoQ10 was well absorbed when P40 was administered even though in the fasting state (11). The safety of CoQ10 has been reported (16).…”
mentioning
confidence: 92%